A neuropsychological rehabilitation service delivery model for South African adults with acquired brain injury (RSDM-SA) - Joosub, Noorjehan; Kruger, Gert; Basson, Pieter (Frontiers in Rehabilitation Sciences, 2024)
In low- and- middle- income countries (LMICs) such as South Africa, a high number of Acquired Brain Injuries (ABIs) and a lack of accessibility to healthcare lead to many survivors of brain injury not receiving the level of healthcare and rehabilitation required. Further, in LMICs life-saving or acute care is prioritized with an inadequate focus on the lifelong effects of ABI. This study used Program Theory to develop a Rehabilitation Service Delivery Model for South African Adults with Acquired Brain Injury (RSDM-SA) that caters for the unique nuances of a resource-constrained and culturally diverse context. The RSDM-SA has four interdependent levels, namely (i) Integration of Relevant Aspects of Explanatory Frameworks (ii) South African Contextual Influences on the Model (iii) Systemic Role players Necessary for the Model and (iv) Evidence-Based Guidelines in a Holistic Rehabilitation Process. The Model is a valuable resource in guiding future research endeavors and its contribution lies in the Model’s focus on quality, accessibility, relevance, and efficiency, all of which are needed in healthcare internationally.